Assessment of Animal Sources of Coronavirus and their Role in Causing Disease in Humans - Alizada, Mohammad Naiem (Journal of Natural Sciences – Kabul University, 2021)
Since December 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has triggered a pneumonia outbreak originating from Wuhan's Huanan seafood market in China. The Coronavirus Disease 2019 (COVID-19) epidemic, caused by SARS-CoV-2, has spread worldwide. According to the Food and Agriculture Organization (FAO) report on December 21, 2020, COVID-19 had affected 215 countries, including Afghanistan. Global statistics estimate the mortality rate at 3.4%. Similar to the SARS coronavirus outbreak in 2002 and the MERS coronavirus outbreak in 2012, bats are the reservoir hosts for these viruses. The intermediate host for SARS is the palm civet, while MERS's intermediate host is the camel. Although the intermediate host for COVID-19 remains unidentified, pangolins are suspected. Early symptoms of COVID-19 include pneumonia, fever, myalgia, and fatigue. This paper aims to review and discuss the animal origins, structure, transmission, pathogenicity, clinical symptoms, and prevention of the coronavirus.